Uji Aktivitas Antioksidan Ekstrak Metanol Kulit Buah Jeruk Nipis (Citrus aurantifolia) Dengan Metode DPPH (1,1-difenil-2-pikrilhidrail) - Alfin Surya; Dinni Febrianti (Jurnal Ilmu Kesehatan Abdurrab, 2023)
The current developments affect many unhealthy lifestyles, such as smoking, lack of sleep, lack of exercise, environmental pollution, radiation, etc. If left unchecked, it will cause several diseases, one of which is cancer and coronary heart disease. Antioxidants are divided into two parts, natural antioxidants and synthetic antioxidants. Synthetic antioxidants in the form of BHA, BHT, PG when consumed continuously will cause side effects to the body, so natural antioxidants are needed which are easy to obtain and relatively inexpensive. We encounter many lime peels in Indonesia, but the processing is not optimal. This study aims to see whether the peel of lime fruit (Citrus aurantifolia) contains antioxidants. Determination of antioxidant levels in this study using the spectrophotometric method. This study used a quantitative descriptive analysis method, namely to calculate the levels of antioxidants in the peel of lime (Citrus aurantifolia). The maceration process was carried out three times for 24 hours. After that, filter the liquid to obtain the methanol extract by separating the thick extract using filter paper. Then, after examination using the Microplate reader LB-941, it was found that the concentration of antioxidants needed to inhibit free radicals by 50% is known as the IC50 value. Lime peel has an IC50 value of 88.2346 ppm. If the IC50 value is less than 50 ppm, a substance shows a very strong antioxidant. If the IC50 value is between 50 and 100 ppm, there will be strong antioxidant activity; if it is between 100 and 150 ppm, there will be moderate antioxidant activity; and if it is more than 150 ppm, the antioxidant activity is weak. This further shows the strong antioxidant activity of the methanol extract of lime peel which has an IC50 value of 88.2346 ppm.